The Self-Efficacy and Kluckhohn's Value Orientations: Core Behavioral Drivers Among Young Tobacco Farmers in Temanggung - Dewi Fortuna, Puri Eka; Hariadi, Sunarru Samsi; Lasiyo; Widiarso, Budi Purwo (UPPM Politeknik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2025)
This study analyzes the primary drivers of tobacco farming behavior among young farmers in Temanggung Regency, Indonesia’s premium tobacco hub. Integrating psycho-cultural approaches—self-efficacy theory (Bandura, 1986) and Kluckhohn’s (1951) cultural value orientation—this research challenges conventional agricultural behavior theories emphasizing environmental factors. Data were collected through a survey of 140 young farmers across 6 core districts, analyzed using Structural Equation Modeling (SEM) and profitability assessment. Key findings reveal Personal factors (particularly self-efficacy: λ=0.743) significantly influence behavior (β=0.706; p<0.01), while environmental factors are insignificant (β=0.147). Kluckhohn’s values especially mastery over nature (mountain land expansion without terracing) and work for livelihood reinforce self-efficacy through cultural internalization. Loyalty among young farmers stems from inherited land ownership (77.14%) and high profitability (R/C ratio 1.44). These findings revise Ajzen’s (1991) theory and propose a